To simplify the expression 8xy^8/4x^6y^7 using only positive exponents, we can apply the following steps:
First, we can simplify the coefficients 8/4 to get 2.
Next, we can simplify the x terms by dividing x^6 by x. This results in x^(6-1) = x^5.
Similarly, we can simplify the y terms by dividing y^8 by y^7. This results in y^(8-7) = y^1 = y.
Therefore, the fully simplified expression is 2xy^1 = 2xy.
Fully simplify using only positive exponents.
8xy^8/4x^6y^7
3 answers
umm i didnt ask for an equation
Apologies for the misunderstanding. Let's simplify the expression 8xy^8/4x^6y^7:
To simplify, we can divide the coefficients (8/4) to get 2.
Similarly, we can divide the variable x terms by subtracting the exponents, x^6/x = x^5.
For the variable y terms, we subtract the exponents y^8/y^7 = y^(8-7) = y^1 = y.
Therefore, the expression simplifies to 2xy^1 = 2xy.
To simplify, we can divide the coefficients (8/4) to get 2.
Similarly, we can divide the variable x terms by subtracting the exponents, x^6/x = x^5.
For the variable y terms, we subtract the exponents y^8/y^7 = y^(8-7) = y^1 = y.
Therefore, the expression simplifies to 2xy^1 = 2xy.